Current State, Challenges, and Opportunities of the School-Based Sexual and Reproductive Health Education in Indonesia: A Systematic Literature Review - Lahope, Genesa; Fathurrahman, Reza (Preventia: The Indonesian Journal of Public Health, 2024)
Sexual and reproductive health education for adolescents remains crucial for Indonesia as it is home for more than 44 million teenagers as of 2022, in its way to anticipate demographic bonus in 2030. Government Regulation no. 61 of 2014 concerning Reproductive Health mandates sexual and reproductive health education in formal and informal education settings. By using a systematic literature review (SLR) method, this study assesses the current state of school-based sexual and reproductive health education in Indonesia. Findings reveal that the delivery of sexual and reproductive health education in Indonesian schools is fragmented, spread across various subjects such as Biology, Sports, Religious, Civic and Moral education classes, as well as extracurricular activities. Key stakeholders, including families, teachers, peers, and school principals, play crucial roles in shaping adolescents' understanding of reproductive health. However, challenges such as cultural taboos, easy access to potentially misleading online information, and inadequate teacher training hinder effective education. In addition, Comprehensive Sexual Education (CSE) has been suggested by WHO to be implemented and integrated in the core curriculum, with programs like SETARA pilot project showing promise in improving adolescent knowledge and attitudes towards reproductive health. However, the success of such programs requires cooperation from various stakeholders and a shift in societal norms regarding adolescent sexuality.